Marketing Needs and Challenges: New Ventures - Aditi, Hamlai (2010)
In this report, I wish to discuss the role that marketing plays in an entrepreneurial venture. I would like to highlight some of the key challenges that new ventures face due to newness, lack of resources, credibility etc. I will also discuss the importance of networking, developing strategic alliances, building a brand identity, developing trust and credibility to a start up. I will critically analyse the concept and importance of entrepreneurial marketing. Lastly, I would like to discuss all of the above mentioned concepts in relation to In-Sight, a new venture.